2014
DOI: 10.1155/2014/238018
|View full text |Cite
|
Sign up to set email alerts
|

A New AILC for a Class of Nonlinearly Parameterized Systems with Unknown Delays and Input Dead-Zone

Abstract: This paper presents an adaptive iterative learning control (AILC) scheme for a class of nonlinear systems with unknown time-varying delays and unknown input dead-zone. A novel nonlinear form of deadzone nonlinearity is presented. The assumption of identical initial condition for ILC is removed by introducing boundary layer functions. The uncertainties with time-varying delays are compensated for with assistance of appropriate Lyapunov-Krasovskii functional and Young’s inequality. The hyperbolic tangent functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Consequently, stabilization problem of control systems with time delay has received much attention for several decades and a large number of research results have been reported in the literature that deal with various analysis and design problems [11][12][13][14][15][16]. However, in the field of AILC, only a few results are available for nonlinear systems with time delays [17][18][19]. In [17], an AILC strategy was developed for a class of scalar systems with unknown time-varying delay and then extended to a class of high-order systems with both time-varying and time-invariant parameters, where the unknown time-varying parameter was estimated in the iterative learning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, stabilization problem of control systems with time delay has received much attention for several decades and a large number of research results have been reported in the literature that deal with various analysis and design problems [11][12][13][14][15][16]. However, in the field of AILC, only a few results are available for nonlinear systems with time delays [17][18][19]. In [17], an AILC strategy was developed for a class of scalar systems with unknown time-varying delay and then extended to a class of high-order systems with both time-varying and time-invariant parameters, where the unknown time-varying parameter was estimated in the iterative learning process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed controller in [17] requires that the uncertainties in the system satisfy local Lipschitz condition and nonlinear parameterized condition such that adaptive learning laws can be used to estimate the unknown timevarying parameters. In [18,19], we designed an AILC scheme for a class of nonlinearly parameterized systems and an RBF NN-based AILC for class of unparameterized systems, respectively, where the systems in two papers are with both unknown time-varying delays and unknown dead zone input. However, all of the aforementioned results are on systems with time delay states.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization problem of control systems with delay has received much attention for several decades and some research results have been reported in the literature (see [3,11,13,[15][16][17][18][19][20][21][22][23]). However, only a few results are available for nonlinear systems, combining with the iterative learning control items, with time delays [11,[24][25][26]. In this paper, under the case that the th iterative state vector ( ) is different from the ( +1)th iterative state vector +1 ( ), that is, +1 ( ) − ( ) ̸ = 0, the iterative learning controller of nonlinear time-delayed systems is designed by using -norm and retarded Gronwall-like inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 6. For system (25) and a given reference ( ), if conditions (9) are true and there exist matrix and functions ,ℎ ( ) and ,ℎ ( ) such that ∫ 0 ,ℎ ( ) = 1, > ℎ, ‖ ‖ is bounded, max(‖ − 1 ‖, ‖ − 2 ‖) ≤ < 1, where is a constant, then system (25) with the iterative learning control law can guarantee that lim →∞ ( ) = ( ) is bounded but ( ) cannot track ( ) on ∈ [0, ℎ] and lim →∞ ( ) = ( ) on ∈ [ℎ, ] for arbitrary initial state (0).…”
mentioning
confidence: 99%